Efficacy of subgingival air-polishing in the non-surgical periodontal therapy of chronic periodontitis - Laura Komlósi; Péter Vályi (Hungarian Dental Association, 2020)
Introduction: The causal treatment of plaque-related periodontal conditions is the removal of the biofilm that forms on tooth surfaces and contains pathogen microorganisms. The efficacy of non-surgical periodontal therapy is currently considered to reach 84%, as the removal of deposits from subgingival area, thus the prevention of reinfections is extremely difficult. The novel air-polishing technology, which is able to reach the microscopic gaps, was adapted to improving a subgingival instrumentation. The purpose of this study was to evaluate the efficacy of air-polishing applied subgingivally through the measurement of clinical parameters. Methods: In this randomized clinical trial 8 from 15 chronic periodontitis patients with a mean age of 51.4 years old were included. Subjects had to show a probing pocket depth (PPD) of ≥ 4 mm in case of at least 2 pockets per quadrant. The treatment was carried out in a split-mouth design: the full-mouth subgingival instrumentation was supplemented by additional glycine powder air-polishing by Perio-Mate instrument (NSK, Japan) on the test side. Parameters were recorded at baseline and 1, 3, and 6 month following treatment. The collected data were evaluated by non-parametric tests (Wilcoxon test within groups and Mann-Whitney U test between groups) using Statistica 13.0 software. Results: At 1 month no significant differences were found between the test and control sides (p > 0.01), nevertheless significant improvement was observed in all investigated parameters in both groups. Further significant improvement was found only in case of test sites at 3 months visit. Similar improvement was recorded at the test sides regardless difficult accessibility of individual sites (multi-rooted teeth, PPD >5 mm), but there were differences at the control sides: less improvement was observed at sites with difficulty in access to the root surface. Conclusion: The additional effect of subgingival air-polishing as a supplementary treatment was observed at 3 months recall. However slight statistically differences supported the adjunctive effect, it seems to the subgingival air-abrasive methods improve the efficacy of mechanical instrumentation of root surface with difficult accessibility.